Micro structural research and hydration heat determination in Portland cement pastes with eletric arc furnace dust (EAFD) - Vargas, Alexandre Silva de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The electric-arc furnace dust (EAFD) is rarely used in the construction industry. In countries where this waste is collected it is used in recovery processes of oxides metals such a Zn, Cd, Pb and Cr. These processes have been not used in Brazil, since the percentage of valuable metallic oxides in the EAFD is not economically feasible (e.g. Zinc with only 13% of mass). There is still need for further research aiming at turning EAFD into a sub product. In this context, the behavior of the waste in Portland cement pastes was evaluated by determining the setting time and the hydration heat as well as by characterizing its mineralogical and micro structure in order to assess its possible use in construction.